Pengaruh Lingkungan Kerja dan Pengembangan Karir terhadap Kinerja Pegawai dengan Mediasi Kepuasan Kerja: Studi pada PT Bank Rakyat Indonesia (Persero) Kc Kendal - Nurul Anandita Rahmaputri; Askar Yunianto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to analyze the effect of work environment and career development on employee performance with mediation of job satisfaction study at PT Bank Rakyat Indonesia KC Kendal. This research is quantitative, with. The population was 200 respondents, with a sampling technique using purposive sampling obtained a sample of 120 respondents. The test used in the study is instrument testing using the pearson correlation validity test by comparing the calculated r value with the table r value, reliability test using the cornbachalpa value of> 0.7, multiple regression analysis, coefficient of determination, f test and t test. The results showed (1) work environment has a positive and significant effect on employee performance, (2) career development has a positive and significant effect on employee performance, (3) work environment has a positive and significant effect on job satisfaction, (4) career development has a positive and significant effect on job satisfaction, (5) job satisfaction has a positive and significant effect on employee performance. Seeing the coefficient of determination of 62.1% on employee performance and 72.1% on job satisfaction while the rest is explained by other variables, further research is recommended to add independent variables to this research model.